2018
DOI: 10.1016/j.ccell.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

MAST1 Drives Cisplatin Resistance in Human Cancers by Rewiring cRaf-Independent MEK Activation

Abstract: Platinum-based chemotherapeutics represent a mainstay of cancer therapy, but resistance limits their curative potential. Through a kinome RNAi screen, we identified microtubule-associated serine/threonine kinase 1 (MAST1) as a main driver of cisplatin resistance in human cancers. Mechanistically, cisplatin but no other DNA-damaging agents inhibit the MAPK pathway by dissociating cRaf from MEK1, while MAST1 replaces cRaf to reactivate the MAPK pathway in a cRaf-independent manner. We show clinical evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 41 publications
(44 reference statements)
2
79
0
Order By: Relevance
“…Through mass spectrometry-based (MS-based) proteomic analysis, we identified hsp90B as a potential binding partner of MAST1 ( Figure 1B). Endogenous interaction between hsp90B and MAST1 was demonstrated by coimmunoprecipitation analysis in cisplatin-resistant sublines of human carcinoma KB-3-1 and lung cancer A549 cells ( Figure 1C) (7). We further explored whether the interaction is limited to the hsp90B isoform by comparing the interaction between MAST1 and hsp90B or hsp90A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Through mass spectrometry-based (MS-based) proteomic analysis, we identified hsp90B as a potential binding partner of MAST1 ( Figure 1B). Endogenous interaction between hsp90B and MAST1 was demonstrated by coimmunoprecipitation analysis in cisplatin-resistant sublines of human carcinoma KB-3-1 and lung cancer A549 cells ( Figure 1C) (7). We further explored whether the interaction is limited to the hsp90B isoform by comparing the interaction between MAST1 and hsp90B or hsp90A.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms underlying cisplatin resistance are complex, and include reduction in the intracellular cisplatin level, enhanced damaged DNA repair, and activation of prosurvival signaling pathways often involving activation of the kinase MEK (2,6). We recently reported that a microtubule-associated serine/threonine kinase 1 (MAST1, also known as SAST170), which is known as a scaffold molecule that links the dystrophin and utrophin complex with microfilaments, is a common critical factor that drives cisplatin resistance in diverse types of human cancer, including head and neck, lung, and ovarian cancers (7,8). MAST1 confers cisplatin resistance through MEK1 reactivation by replacing its conventional kinase cRaf when cisplatin disrupts the interaction between MEK1 and cRaf (7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, MEK1 reactivation is contributed to cancer cell resistance to cisplatin. This occurs by cisplatin inducible effects on dissociation of CRAF from MEK1 and further replacing CRAF with microtubule‐associated serine/threonine kinase 1 (MAST1) to reactivate MAPK pathway, so inhibition of MAST1 by agents like lestaurtinib could restore cisplatin sensitivity (Jaykumar et al, ; Jin et al, ).…”
Section: Combination Therapy Is a Promising Strategy For Targeting Mamentioning
confidence: 99%